2019
DOI: 10.1111/ner.12784
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Subcutaneous Nerve Stimulation for Back Pain Due to Failed Back Surgery Syndrome: The SubQStim Study

Abstract: The results indicate that the addition of SQS to OMM is more effective than OMM alone in relieving low back pain at up to nine months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In patients with failed back surgery syndrome, this study found positive effects on pain measured with a VAS score and an improvement in the patients' global impression of change score. However, this study had unclear risk of bias in three of five categories in the risk of bias tool .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In patients with failed back surgery syndrome, this study found positive effects on pain measured with a VAS score and an improvement in the patients' global impression of change score. However, this study had unclear risk of bias in three of five categories in the risk of bias tool .…”
Section: Discussionmentioning
confidence: 84%
“…In one trial that measured pain relief with sphenopalatine ganglion stimulation for chronic cluster headaches, significantly more patients achieved pain relief through full stimulation compared to subperception or sham stimulation ( p < 0.0001) . In patients with failed back surgery syndrome, one study compared subcutaneous nerve stimulation to optimized medical management . This trial reported a significant reduction in pain for patients receiving the intervention plus optimized medical management (33.9% of patients achieved a pain reduction of 50% or greater, measured with a VAS) compared with a control group of patients receiving optimized medical management alone (1.9%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence and cost of LBP, which has been turned into a general problem, shows an increasing trend in societies (11). LBP epidemiology has been studied in adults more widely, but there are few studies on this problem in children (12).…”
Section: Contextmentioning
confidence: 99%
“…Good outcomes have been reported applying PNFS in the management of CLBP in patients with or without a medical history of lumbosacral spinal surgery and refractory to common therapies 14‐17 . Recent evidence from randomized controlled trials (RCTs) indicates that the use of PNFS may significantly improve pain outcomes when used as a primary technique or as an add‐on therapy to SCS 18,19 …”
Section: Introductionmentioning
confidence: 99%